Pengaruh Moderate-Intensity Continuous Training (MICT) Terhadap Fungsi Kognitif Tikus Wistar yang Diberikan Paparan Cahaya Light-Emitting Diode (LED) - Nahan, Elmo; Farah Fauziyah Radhiyatulqalbi Ahmad; Surbakti, Ranintha Br.; Margaretha Yayu Indah Anugerahny; Dian Mutiasari (Fakultas Kedokteran Universitas Trisakti, 2026)
Background Sleep disturbances due to circadian rhythm disruption, including night time exposure to Light-Emitting Diode (LED) light, have been associated with cognitive decline. Moderate-Intensity Continuous Training (MICT) is known to improve cognitive function through various neuroplastic mechanisms. However, evidence regarding its protective effects of MICT against LED-induced cognitive impairment remains limited. Methods This study used a true experimental pre-test and post-test control group design. A total of 24 male Wistar rats (6-8 weeks old, 150-200 g) were randomly divided into four groups: control, LED (24-hour/day LED exposure), MICT (moderate-intensity swimming 5 times/week), and MICT+LED for 4 weeks. Cognitive function was assessed using the Y-Maze spontaneous alternation test before and after the intervention. Data were analyzed using Shapiro-Wilk, Levene, Paired T-Test, Mann-Whitney, Kruskal-Wallis, and Repeated Measures ANOVA with p<0.05. Results The LED group showed a decrease in cognitive function from 43.50 to 40.00 (p=0.102), while the MICT group exhibited a significant increase from 18.75 to 31.25 (p=0.027). The MICT+LED group experienced an increase from 29.00 to 35.00 (p=o.385). Kruskal Wallis test showed no significant differences between groups (p=0.071), while Repeated Measures ANOVA indicated a significant effect of time on cognitive changes (p<0.001). Conclusions LED exposure tends to impair cognitive function, although not significantly. MICT enhanced cognitive function and showed potential as a protective intervention against LED-induced cognitive decline.Keywords: Moderate-Intensity Continuous Training; Light-Emitting Diode; cognitive function; Wistar rats; circadian rhythm.